2022
DOI: 10.3390/plants11050627
|View full text |Cite
|
Sign up to set email alerts
|

Mining of Potential Gene Resources for Breeding Nutritionally Improved Maize

Abstract: Maize is one of the leading food crops and its kernel is rich in starch, lipids, protein and other energy substances. In addition, maize kernels also contain many trace elements that are potentially beneficial to human health, such as vitamins, minerals and other secondary metabolites. However, gene resources that could be applied for nutrient improvement are limited in maize. In this review, we summarized 107 genes that are associated with nutrient content from different plant species and identified 246 ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…The proper ratio of unsaturated to saturated fatty acids in maize oil is considered as a character of high-quality oil for human health ( Han et al., 1987 ; Benitez et al., 1999 ; Lambert et al., 2004 ). In addition, the high energy and proportion of polyunsaturated fatty acids is highly valued for animal feed, industrial applications and an alternative to fossil fuels ( Hou et al., 2022 ). Thus, the ability to improve oil quantity and quality has been a key target for plant breeding and biotechnology-assisted improvement ( Yang et al., 2012 ; Li et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The proper ratio of unsaturated to saturated fatty acids in maize oil is considered as a character of high-quality oil for human health ( Han et al., 1987 ; Benitez et al., 1999 ; Lambert et al., 2004 ). In addition, the high energy and proportion of polyunsaturated fatty acids is highly valued for animal feed, industrial applications and an alternative to fossil fuels ( Hou et al., 2022 ). Thus, the ability to improve oil quantity and quality has been a key target for plant breeding and biotechnology-assisted improvement ( Yang et al., 2012 ; Li et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that Gras23 may likewise be involved in plant development, with a role involving the trans‐differentiation of epithelial cells of the maize scutellum into totipotent, embryogenic cells. Gme1 is an enzyme involved in secondary carbon metabolism and reversibly converted GDP‐α‐ d ‐mannose to GDP‐β‐ l ‐galactose (Woodhouse et al ., 2021 ), an intermediate step in the synthesis of ascorbic acid (Hou et al ., 2022 ; Xiao et al ., 2021 ), a media additive in some maize transformation methods used to modulate stress response (Jones et al ., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…While the coding sequences for both genotypes displayed a high degree of conservation, the B73 and A188 alleles of Wox2a only shared approximately 69% identity in their promoter sequence. Furthermore, B73 and A188 were grouped into separate clades (Figure 1b) when a multiple sequence alignment was performed with a diverse group of maize lines (Hufford et al, 2021;Yu et al, 2008). When both coding sequences were expressed under the ZmUbi1 promoter, it was observed that the B73 and A188 Wox2a gene sequences performed identically (Table 1) according to Fisher's exact test, with P-value critical threshold set by Bonferroni's correction to adjust for multiple comparisons (P ≤ 0.05).…”
Section: Comparison Of B73 and A188-derived Wox2a Gene Sequencesmentioning
confidence: 99%
“…Based on the understanding of the health effects of whole grains and the nutritional and health components of cereals, more active grain varieties can be cultivated through metabolomics analysis and molecular breeding. [153][154][155][156] Moreover, the development of suitable whole grain food processing technology by controlling flavor and the content and physiochemical properties of active ingredients will help to further the promotion of a healthy whole grain diet in the future.…”
Section: Reviewmentioning
confidence: 99%